Factors Affecting Physical Education Teacher Performance: Work Environment and School Facilities and Infrastructure - Siska Aprelyani (Siber International Journal of Sport Education, 2025)
Literature Review of factors of work environment and school infrastructure affecting the performance of physical education teachers is a scientific article with the aim of analyzing whether teacher performance is influenced by the work environment and school infrastructure. Qualitative approach method with literature review method to explore and analyze the relationship between work environment, school infrastructure and teacher performance. The results of this article are: 1) Work environment affects teacher performance; 2) School infrastructure affects teacher performance. Apart from these 2 exogenous variables that affect the endogenous variable of teacher performance, there are many other factors including communication, discipline, organizational climate.